2005
DOI: 10.1073/pnas.0508693102
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein (apo) E4 enhances amyloid β peptide production in cultured neuronal cells: ApoE structure as a potential therapeutic target

Abstract: Apolipoprotein (apo) E4 is a major risk factor for Alzheimer's disease, and many studies have suggested that apoE has isoformspecific effects on the deposition or clearance of amyloid ␤ (A␤) peptides. We examined the effects of apoE isoforms on the processing of amyloid precursor protein (APP) and on A␤ production in rat neuroblastoma B103 cells stably transfected with human wild-type APP695 (B103-APP). Lipid-poor apoE4 increased A␤ production in B103-APP cells to a greater extent than lipid-poor apoE3 (60% vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
204
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 242 publications
(210 citation statements)
references
References 82 publications
6
204
0
Order By: Relevance
“…Replacing Arg-61 with Thr in apoE4, which abolishes domain interaction, completely inhibited apoE4-mediated stimulation of A␤ production (125). Excitingly, the apoE4 effect was abolished by treating the apoE4 with small molecules predicted to interact with the N-terminal region of apoE4 (but not apoE3) in the vicinity of Arg-61 and Arg-112 and disrupt domain interaction (125).…”
Section: Apoe4 Neuropathology In the Context Of A␤mentioning
confidence: 99%
See 2 more Smart Citations
“…Replacing Arg-61 with Thr in apoE4, which abolishes domain interaction, completely inhibited apoE4-mediated stimulation of A␤ production (125). Excitingly, the apoE4 effect was abolished by treating the apoE4 with small molecules predicted to interact with the N-terminal region of apoE4 (but not apoE3) in the vicinity of Arg-61 and Arg-112 and disrupt domain interaction (125).…”
Section: Apoe4 Neuropathology In the Context Of A␤mentioning
confidence: 99%
“…Many studies have focused on the role of apoE in stimulating A␤ deposition or clearance (63,64,75,76). However, apoE4 also enhances A␤ production; apoE3 does so to a lesser extent (125). In rat neuroblastoma B103 cells stably transfected with human wild-type APP695, lipid-poor apoE4 stimulated A␤ production 60%, compared with only 30% by apoE3, and robustly stimulated APP recycling as well.…”
Section: Apoe4 Neuropathology In the Context Of A␤mentioning
confidence: 99%
See 1 more Smart Citation
“…The linking of apoE4 domain interaction and astrocyte dysfunction represents a new paradigm for the association of apoE4 with neurodegenerative diseases and indicates that apoE4 domain interaction represents a viable therapeutic target. It was recently reported that disrupting domain interaction with small molecules abolishes the apoE4 enhanced Aβ production in cultured cells [51]. The relative contributions of molten globule formation and the lack of cysteine in apoE4 will await the generation of mice specific for these features, which are currently in progress.…”
Section: Reduced Cholesterolssecretionmentioning
confidence: 99%
“…Binding (19) ) showing amino acid residues that distinguish between the isoforms. Arg112 facilitates bridge formation (Arg61-Glu255) leading to domain interaction in the apoE4 isoform.…”
Section: Arg158mentioning
confidence: 99%